The Sacramentality of the World and the Mystery of Freedom Hans Urs von Balthasar, Reader of Origen - Zocchi, Elisa (Adamantiana, 2021)
The book offers the first in-depth study of Origen's presence in Hans Urs von Balthasar, not only considering his books on Origen, but also analyzing Origenian ideas that played a decisive role in his theological building. Starting from the historical context, the book connects Balthasar's reading of Origen to the main issues of 20th-century Catholic theology and to theologians like Henri de Lubac, Karl Rahner, and Karl Barth. The book moves then to the main theological elements traceable in the relationship between Origen and Balthasar: Eros, spiritual senses, freedom, and universal salvation. Throughout these ideas, Balthasar's attitude towards Origen emerges as dynamic and multifaceted.